FOURTH GRADE STUDENTS’ PERCEPTION OF ANIMALS IN RURAL ALANYA - Hilmi DEMİRKAYA and Burcu ALPARSLAN (International Journal of Eurasia Social Sciences, 2017)
This study is focusing on the determine the fourth grade students’ perceiving of some animals from the view of positive and negative perpectives. The study group was composed of 23 fourth grade students (11 of whom were female and 12 of whom were male) attending the Kızılcaşehir (Alanya) primary school in the 2015-2016 academic year. The data collected by means of open-ended questions were evaluated through content analysis. Face to face closed interview with every participants individually were carried out. According to the findings obtained in this research; while 12 of the participants’ family have at least a livestock 11 of them haven’t any livestock, 11 of the students have at least a pet 12 of them haven’t any pet. Most of the participants said that they feared of tortoises, most of them said that they disgusted of snakes, on the other hand almost all of them said that they liked the ants.